Cardiovascular protection effect of a Northeastern Brazilian lyophilized red wine in spontaneously hypertensive rats - Natália T.M. Calzerra; Mayara P. Melo; Pablo F. Santos; Kívia S. Assis; Priscilla M.P. Maciel; Renata L.P. Vieira; Fátima de L.A.A. Azevedo; Angela M.T.M. Cordeiro; Bruno R.L.A. Meireles; Islania G.A. Araújo; Robson C. Veras; Isac A. Medeiros (Journal of Functional Foods, 2022)
Moderate consumption of wine has a protective effect on the cardiovascular system. This study proposes to investigate the cardiovascular protective effect of the lyophilized red wine RIO SOL Cabernet-Sauvignon (LRW-RSCS), produced in Northeastern Brazil, in SHR. Sixteen different phenolic compounds, such as gentisic acid, catechin, and resveratrol were identified in LRW-RSCS using high-performance liquid chromatography. LRW-RSCS presented anti-radical activity. Six-week treatment of SHR with LRW-RSCS (100 or 300 mg/Kg/day intra-gastrically) reduced blood pressure and hypercontractility, and improved mesenteric resistance artery endothelial function. The protective effect of LRW-RSCS on endothelial function, mediated relaxation involving both higher endothelial-NO and -EDHF. LRW-RSCS intake reduced vessel wall thickness, media-to-lumen ratio, collagen vascular deposition, and vessel oxidative stress. LRW-RSCS also attenuated platelet hyper aggregation and ROS generation. The results demonstrate that LRW-RSCS from Northeastern Brazil presents cardiovascular protective effect in SHR, at least in part by decreasing oxidative stress.